A modular and community-driven FAIR teaching and training handbook for higher education institutions - Claudia Engelhardt; Aoife Coffey; Yuri Demchenko; Federica Garbuglia; Mijke Jetten; Martijn Kersloot; Valerie McCutcheon; Stephan Nylinder; Britta Petersen; Birgit Schmidt; Hugh Shanahan; Armin Straube; et al. (Liber Quarterly: The Journal of European Research Libraries)
The FAIR principles have had a transformative effect on research data management. Based on this, there is a growing need to increase awareness, understanding and adoption of this topic in higher education at all levels and to provide guidance on how to teach it in bachelor’s, master’s and doctoral degree programmes. This article discusses a collaborative, co-creative approach to construct a body of knowledge and a set of tools addressing this gap, that have been summarised in a teaching and training handbook. We outline how the handbook was written using a large community of volunteers working together remotely. We then discuss the overall content of the handbook, including lesson plans, guidance on how to develop appropriate lessons, a detailed overview of FAIR-related competencies and learning outcomes, and guidelines on how to implement FAIR within an institution. Finally, we discuss the uptake of the handbook, and examples of how the handbook has or could be used in a variety of different training settings.